Analisis Pengaruh Biaya Produksi Dan Sosial Media Terhadap Permintaan Produk makanan Cepat Sajidi Kota Medan Pasca Pandemi Covid-19 (Studi Kasus Locabite Burger Box) - Ginting , Nauval Haiban; Harmain, Hendra; Atika, Atika (CV. ITTC INDONESIA, 2023)
This research aims to examine the analysis of the influence of production costs and social media on the demand for fast food products in Medan city post-COVID-19 pandemic, both partially and simultaneously. This study uses a quantitative method with data collection using the Likert scale method. The subjects used in this study were 100 people from Locabite Burger Box, taken using the Purposive Sampling Technique. Data analysis techniques were conducted through the IBM SPSS statistic 25 program. The results of this study indicate that first, the production cost variable has a significant influence on the demand for fast food products as seen from the statistical results showing a sig value of 0.000 < 0.05 and tcount > ttable, which is 7.176 > 1.661. Second, the social media variable has a significant influence on the demand for fast food products as seen from the statistical results showing a sig value of 0.001 < 0.05 and tcount > ttable, which is 7.428 > 1.661. And third, simultaneous results show that there is a joint influence of production costs and social media on the demand for fast food products as seen from the statistical results showing a sig value of 0.001 < 0.05 and fcount > ftable, which is 11.251 > 3.088.